Pengembangan Rational Beliefs Untuk Menangani Siswa Yang Tawuran Di Sekolah - Faozi, Charis; Iswati, Iswati; Sulistiyoningrum, Renny (Universitas Muria Kudus, 2018)
Youth and solidarity are two very related things that we often encounter in a friendship relationship. A high sense of solidarity and not accompanied by emotional maturity in adolescents make one of the factors causing rampant brawling among teenagers recently. The existence of irrational beliefs that make adolescents interpret the sense of solidarity as an excuse to conduct brawl encourages authors to use the rational belief approach as one effort to minimize brawl behavior among adolescents. Rational beliefs help us to change the irrational beliefs that teenagers have become rational beliefs that of course can change the adolescent's perspective on the meaning of solidarity itself as a positive feeling in a friendship relationship not as an excuse for unhealthy behavior. It will also encourage a new and effective philosophy in the relationship of friendship that exists in a larger sphere.